Análisis técnico de la estrategia de manufactura y su incidencia en el sistema de producción en la empresa BALPLANT Cia. Ltda. del cantón Santo Domingo - Galeas Rodriguez, Jessica Carolina (2018)
This research is based on a technical analysis that has as main objective to determine a manufacturing strategy that in the medium or long term allows to achieve the sustainable development of the company, improving the productivity indicators. Through the application of methods engineering an analysis and diagnosis of the current situation of the production processes of the company was carried out, with this method the areas with flaws were detected in which they should carry out actions that allow to improve the flow of Production processes and productivity indices. For this, the proposal of a production strategy model called Manufacturing Strategy Model-MSM is presented, with which the aim is to improve the competitiveness of the company Balplant Cía. Ltda., this model is based on two fundamental elements that compose the Production strategy: competitive priorities and strategic production decisions. The implementation of this proposal is expected to minimise the unproductive times, reprocessing and waste generated in the process of building glued blocks and thus achieve sustainable development.